Uncertain chances : science, skepticism, and belief in nineteenth-century American literature - Lee, Maurice S. (Oxford University Press, 2012)
The role of chance changed in the nineteenth century, and American literature changed with it. Long dismissed as a nominal concept, chance was increasingly treated as a natural force to be managed but never mastered. New theories of chance sparked religious and philosophical controversies while revolutionizing the sciences as probabilistic methods spread from mathematics, economics, and sociology to physics and evolutionary biology. Chance also became more visible in everyday life, as Americans attempted to control its power through weather forecasting, insurance policies, military strategy, a.